Hospital care for mental health and substance abuse conditions in Parkinson's disease. Issue 12 (December 2016) - Willis, Allison. W.; Thibault, Dylan P.; Schmidt, Peter N.; Dorsey, E. Ray; Weintraub, Daniel
ABSTRACT: Objective: The objective of this study was to examine mental health conditions among hospitalized individuals with Parkinson's disease in the United States. Methods: This was a serial cross‐sectional study of hospitalizations of individuals aged ≥60 identified in the Nationwide Inpatient Sample dataset from 2000 to 2010. We identified all hospitalizations with a diagnosis of PD, alcohol abuse, anxiety, bipolar disorder, depression, impulse control disorders, mania, psychosis, substance abuse, and attempted suicide/suicidal ideation. National estimates of each mental health condition were compared between hospitalized individuals with and without PD. Hierarchical logistic regression models determined which inpatient mental health diagnoses were associated with PD, adjusting for demographic, payer, geographic, and hospital characteristics. Results: We identified 3, 918, 703 mental health and substance abuse hospitalizations. Of these, 2.8% (n = 104, 437) involved a person also diagnosed with PD. The majority of mental health and substance abuse patients were white (86.9% of PD vs 83.3% of non‐PD). Women were more common than men in both groups (male:female prevalence ratio, PD: 0.78, 0.78‐0.79, non‐PD: 0.58, 0.57‐0.58). Depression (adjusted odds ratio 1.32, 1.31‐1.34), psychosis (adjusted odds ratio 1.25, 1.15‐1.33), bipolar disorder (adjusted odds ratio 2.74, 2.69‐2.79), impulse control disorders (adjusted odds ratio 1.51, 1.31‐1.75), and mania (adjusted odds ratio 1.43, 1.18‐1.74) were more likely among PD patients, alcohol abuse was less likely (adjusted odds ratio 0.26, 0.25‐0.27). We found no PD‐associated difference in suicide‐related care. Conclusions: PD patients have unique patterns of acute care for mental health and substance abuse. Research is needed to guide PD treatment in individuals with pre‐existing psychiatric illnesses, determine cross provider reliability of psychiatric diagnoses in PD patients, and inform efforts to improve psychiatric outcomes. © 2016 International Parkinson and Movement Disorder Society.